Targeting Endothelin in Alzheimer's Disease: A Promising Therapeutic Approach. (7th September 2021) - Sharma, Shiwali; Behl, Tapan; Kumar, Anoop; Sehgal, Aayush; Singh, Sukhbir; Sharma, Neelam; Bhatia, Saurabh; Al-Harrasi, Ahmed; Bungau, Simona
Abstract : Endothelin is a chemical mediator that helps in maintaining balance within the blood-brain barrier by regulating the levels of toxicants and molecules which pass through the brain, suggesting that a rise in its production determines Alzheimer's disease. The inequity in the amyloid β occurs due to a problem in its clearance from the brain initiating the production of reactive oxygen species and superoxide that activates a cascade wherein the release of inflammatory mediators and various enzymes like endothelin-converting enzymes take place. Furthermore, the cascade increases the levels of endothelin in the brain from endothelial cells. Endothelin levels are upregulated, which can be regulated by modulating the action of endothelin-converting enzymes and endothelin receptors. Hence, endothelin paves a pathway in the treatment of Alzheimer's disease. In this article, we have covered various mechanisms and preclinical studies that support and direct endothelin involvement in the progression of Alzheimer's disease by using various search tools such as PubMed, Science Direct, and Medline. Conclusive outcome data were extracted that all together defy contrivance pathways, potential drugs, endothelin receptors, and endothelin enzymes in our article giving profound importance to target endothelin for prevention and treatment of Alzheimer's disease.